Inherent vs. Induced Loop Gain Abnormalities in Obstructive Sleep Apnea - Deacon-Diaz, Naomi; Malhotra, Atul (Frontiers in Neurology, 2018)
Unstable ventilatory chemoreflex control, quantified as loop gain, is recognized as one of four key pathophysiological traits that contribute to cause obstructive sleep apnea (OSA). Novel treatments aimed at reducing loop gain are being investigated, with the intention that future OSA treatment may be tailored to the individual’s specific cause of apnea. However, few studies have evaluated loop gain in OSA and non-OSA controls. Therefore it is currently uncertain whether loop gain is indeed elevated in OSA independent of morphological factors known to alter ventilatory chemoreflex control. It is also uncertain what mechanisms may contribute to elevated loop gain in OSA, and whether abnormalities are inherent or induced, and therefore reversible. Thus it is imperative that these questions be answered before treatments aimed at reducing loop gain can be developed. This review addresses the evidence that loop gain is elevated in untreated OSA patients, primarily due to intermittent hypoxia induced neuroplasticity in ventilatory chemoreflex control. Studies which have failed to exhibit elevated loop gain in treated OSA patients may be due to the treatment reversible nature of ventilatory neuroplasticity. Areas where further research are required are highlighted, and lastly, how understanding the mechanisms contributing to elevated loop gain in OSA can direct development of treatments aimed at reducing loop gain are discussed.